Mentoring At-Risk Youth: an Examination of Strain and Mentor Response Strategies - Wesely, Jennifer K. (American journal of criminal justice, 2017)
Mentoring is a popular and widespread intervention for at-risk youth that can positively influence this population’s adaptation to stressors and increase overall resilience. Yet there is a lack of attention to how mentoring relationships work or the attributes of mentoring that contribute to successful outcomes. In this study, we employ qualitative in-depth interviews with mentors in a school-based program to learn about their perceptions of the strain experienced by their mentees, and how they respond to it during sessions. We focus on emotional regulation, conflict resolution, future orientation, and active listening - four positive coping strategies associated with enhanced resilience among at-risk youth. This study considers how these positive strategies fit into mentors’ descriptions of their approaches and the implications for intervention programming.